STUDI DESKRIPSI MUSIKAL KESENIAN LUKAH GILO DIKENAGARIAN GUNUANG BUNGKUAK LUMPO KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Radhiyah Radhiyah; Jagar Lumban Toruan; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2017)
AbstractThe research aimed at finding and describing the song of Lukah Gilo intrinsically and exrtrinsically at Kenagarian Gunuang Bungkuak Lumpo Kecamatan IV jurai Pesisir Selatan region from the musical feet. This research was qualitative using descriptive approach based on the theory dealing with rhythm, melody, and the structure of the song. The data were derived from the performance of Lukah Gilo in general, transcribed the song and then the data were analyzed. The research shows that the Lukah Gilo is performed occasionally. In the performance there are some poem (andai-andai or mantra) singing accompanied by Rabab Pasisia, Rabana and Tambourine. The song is like a poem consist of eleven stanza, each of the stanza has the motive up to 45, 16 phrases. The pitch which is uses are F, G, A, Bes dan C’ with F= Do. There are five internal: that is Prime Perfect (P1), Second Minor (m2),Second Mayor (M2), Tarts Mayor (M3) anda Kwart Perfect (P4 The structure of the poem Lukah Gilo consists of threeparts A, B dab B.Keywords: Study Of Musical Description, Lukah Gilo Art